2018
DOI: 10.1515/hukin-2017-0193
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rule Modifications on Elite Basketball Teams’ Performance

Abstract: Rule modifications in basketball are used to develop the sport, and FIBA changes the basketball regulations periodically and constantly in search of a more attractive game. The objectives of this study were as follows: i) to characterise and identify the technical-tactical performance indicators which discriminated the game style according to the effect of rule modifications; and ii) to analyse the persistence of these indicators according to rule modifications over time. Analyses were made of all the editions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
2
23
0
3
Order By: Relevance
“…In official games played under the rules of FIBA, game-related statistics are recorded according to the regulations established by FIBA 1 , which ensure intra-and inter-operator reliability 2 . In addition, a high level of inter-rater reliability has been repeatedly confirmed (kappa coefficient above 0.89) 4,17,21,25 , so that official scores are treated as reliable in basketball studies 26,27 . Game-related statistics of each game were analyzed separately for the winning and losing teams (298 cases were analyzed in total).…”
Section: Sample and Variablesmentioning
confidence: 89%
See 1 more Smart Citation
“…In official games played under the rules of FIBA, game-related statistics are recorded according to the regulations established by FIBA 1 , which ensure intra-and inter-operator reliability 2 . In addition, a high level of inter-rater reliability has been repeatedly confirmed (kappa coefficient above 0.89) 4,17,21,25 , so that official scores are treated as reliable in basketball studies 26,27 . Game-related statistics of each game were analyzed separately for the winning and losing teams (298 cases were analyzed in total).…”
Section: Sample and Variablesmentioning
confidence: 89%
“…Game-related statistics have been studied to scientifically illustrate the games in various categories: the Olympic Games for men 3,4,5 and women 6 , FIBA Basketball World Cup for men 7 , professional leagues for men 8,9,10 and women 11,12,13 , and international tournaments for youth athletes 14,15 . In addition, game-related statistics have been analyzed in various contexts such as effects of rule changes 16,17 , age and sex differences 18,19 , and relationship with physical fitness 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, official box scores are treated as reliable in basketball studies [16,17], because the recording process is executed according to the regulations established by FIBA [18], and a high level of inter-rater reliability (kappa coefficient above 0.89) has been repeatedly confirmed [2,19,20,21]. Game-related statistics of each game were analyzed separately for the winning and losing teams, so that 268 cases were analyzed in total.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical modelling in team sports has been an important analytical tool to predict match outcome and the evolution of team's performance [1][2][3][4]. In particular, examination of match-related performance indicators in basketball has enabled modelling to identify winning and losing teams [5], best and worst teams [6], the influence of contextual-related variables [7], the effect of consecutive games [8] or the impact of rule changes [9][10][11] on team's performances. Typically, these analyses have been conducted over a season [5,7], however, analysing team performances over many seasons may identify the evolution and impact of changes on a team's style of play [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified 2-point field goals made and/or defensive rebounds and/or assists as the most prominent team indicators that result in winning basketball matches [5,[12][13][14]. However, the style of basketball match play has likely evolved due to changes in rules (i.e., an increase in the 3-point line distance), match pace (i.e., greater number of ball possessions per match), and team focus on particular match indicators such as turnovers, 3-point field goals attempted or fouls [10,11,15]. A greater understanding of how basketball performances have evolved, particularly those teams that have adapted behaviours to win consistently over many seasons [16], would assist teams for greater and long-term success.…”
Section: Introductionmentioning
confidence: 99%